2003
DOI: 10.1001/archinte.163.9.1053
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Total Cholesterol Level as a Risk Factor for Alzheimer Disease

Abstract: In this large, population-based cohort, baseline and long-term average serum total cholesterol levels were not associated with the risk for incident AD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
167
1
3

Year Published

2003
2003
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 263 publications
(177 citation statements)
references
References 33 publications
6
167
1
3
Order By: Relevance
“…40 -43 High cholesterol levels were associated with an increased risk of AD or cognitive impairment in several cross-sectional and prospective studies, 41,43-45 although no association was found in the Framingham cohort, 46 and established AD cases had lower cholesterol levels in other studies. 47,48 Cholesterol levels were influenced by APOE genotype, sex, age, and stage of AD.…”
Section: Markers Related To Cholesterol Metabolism and Vascular Diseamentioning
confidence: 99%
“…40 -43 High cholesterol levels were associated with an increased risk of AD or cognitive impairment in several cross-sectional and prospective studies, 41,43-45 although no association was found in the Framingham cohort, 46 and established AD cases had lower cholesterol levels in other studies. 47,48 Cholesterol levels were influenced by APOE genotype, sex, age, and stage of AD.…”
Section: Markers Related To Cholesterol Metabolism and Vascular Diseamentioning
confidence: 99%
“…As expected, analysis of the lipidic parameter for the HD group revealed a significant modification of the plasma lipidic profile, with an increase of 1000% in LDL-C, 400% in TC, and 130% in TG levels. Many epidemiological (27) and in vivo studies using wild type and transgenic animals such as mice (1,(28)(29)(30) have supported a strong association between the pathogenesis of AD and circulating LDL-C. Chen et al have shown that increased levels of LDL-C can lead to disturbances in the endolysosome structure in neurons and, following APP internalization, can promote the accumulation of Aβ deposits (31). In our experiment, despite an approximately fourfold increase in TC plasma levels, we observed no marked change in brain TC.…”
Section: Discussionmentioning
confidence: 99%
“…22 Furthermore, it has been shown that hypercholesterolemia accelerated AD pathology in transgenic animal models, 23 being also an early risk factor for AD in epidemiology studies. 24,25 These data point out the possibility that treating human patients with these cholesterol-lowering drugs might either reduce the risk of developing AD or help to treat it.…”
Section: Discussionmentioning
confidence: 99%